Optimizing Waste Management to Increase Community Awareness in Arjosari Sub-village, Ampelgading-Tirtoyudo - Wibowo, Joko; Puadi, Hairul (Lembaga Penerbitan dan Publikasi Ilmiah, 2024)
Waste management is one of the environmental problems often faced by marginalized communities. This activity is a research-based activity intended to increase awareness of community participation-based waste management in Arjosari Village, Tirtoyudo. The method used is PAR or participatory action research which seeks to strengthen the role and participation of the community in every line of the change movement. The waste management program in Arjosari Village is based on the inadequacy of waste management in the village. Not only that, there are many illegal waste dumps that can pollute the environment due to public awareness about the importance of protecting natural ecosystems. We have implemented programs to overcome this in several waste management projects, namely establishing a waste sorting system, producing compost and eco-enzyme products from organic waste. These projects involve the direct participation and role of the entire community.